La melancolía en la antigüedad : el problema XXX en Aristóteles (EDICIONES UC, 2017)
This work presents a detailed and innovative research on melancholy in Antiquity. Preceded by an introduction, which allows the reader to trace the semantic evolution of the word from its first testimonies in Greek literature to Aristotle, the study delves into the concept of melancholy and the melancholic individual in Hippocratic medicine and in the Stagirite treatises. In addition, the book includes a bilingual Greek-Spanish translation of Pseudo-Aristotle's Problem XXX, which is the first work on melancholy in world literature.